PERANCANGAN INTERIOR GRACEFULLY GRACE PRESCHOOL DI JAKARTA - Janah, Adilla Nur; Nadaa, Zulfiska (Anggada : Jurnal Desain dan Seni, 2021)
During development, many preschoolers need stimulation and support from the surrounding environment. Because at that time early childhood entered the golden age or golden age. Early childhood education is needed to help the spiritual and physical development of early childhood before entering elementary school education. The efforts made are formal and informal preschools such as Kindergarten, Playgroup, RA and so on. The preschool requires a good quality place so that children can grow and develop both physically and mentally. This design aims to implement interior elements that are in accordance with interior rules and improve the quality of education in early childhood and prioritize comfort, safety and health, for that many aspects of the interior (dimensions, shape of furniture, materials, colors applied in the interior) that must be considered so that the goals to guide, educate and support children's development can be achieved. The method used is interviews, field data and literature and analysis of existing problems. From these results the concept used in this design is to use the style and theme of Natural Cheerful Contemporary with the impression to be applied is fun, safe and comfortable.